Determinants of Financial Performance of Companies Listed on the Indonesian Institute For Corporate Governance - Muhammad Tri Luthfillah; Isni Andriana; Abdul Bashir; Didik Susetyo; Mukhtaruddin (Indonesian Journal of Business Analytics, 2024)
The aim of this study was to examine and analyze the impact of Environmental Management Accounting and Environmental Performance on Financial Performance. The study focused on companies that participated in the CGPI program, using secondary data from the period 2018-2023. The sampling method employed was purposive sampling, with a total of 12 companies and 72 data observations. The analysis was conducted using quantitative methods and Eviews panel data regression. The findings indicated that both Environmental Management Accounting and Environmental Performance had a significant positive effect on Financial Performance.